Interaction Between Hydrodynamics and Chemical Reaction Rate in a Vertical Gas-Slurry Cocurrent Turbulent Tube Reactor. II. Applications - Cantero, Héctor (2000)
The behavior of an isothermal, vertical tube reactor in a dispersed bubble flow environment in either upflow, downflow or upflow-downflow configurations is examined, using the performance indicators defined in Part I. The hydrogenation of a coalescent organic system, like the one found in the mild hydrogenation process of soybean oil, is taken as a reference system. The likelihood of the axial changes of the local gas-slurry mass transfer efficiency and, then, of the controlling regimes of the process rate is discussed. Further effects of the configuration on the conversion of the liquid reactant, the unconverted mass of the gas phase, and the pressure drop are also analyzed.